Qawaid al-Tarjih fi al-Juz’i 30 fi Tafsir Ahkam Al-Qur’an - MAHER BIN GHAZALI (Studia Quranika, 2021)
This research deals rules of preference in tafsir of rulings of the Qur’an by Imam Ibn al-Arabi, and their applications to the thirtieth part of the Qur’an, as he is one of the exegetes who proficiently employed the rules of preference in their tafsir, and the few who dealt with this aspect in an applied manner, as the researcher tried to use the inductive and analytical approach in order to derive of preference rules that Ibn al-Arabi relied on his tafsir, and the researcher reached these rules of preference, which is by using rules in of preference by the year, as well as rules in of preference by impact, then Rules for of preference in the language, a rule in of preference in the Qur’an context, as well as a rule of preference by Writing the Ottomani Qur’an